Digital Storytelling to Improve Speaking Skill - Fadhilah Zamzam (Universitas Cokroaminoto Palopo, 2020)
Problem identified in this research was the speaking ability of first semester students at international class of Communication Science Department of Tadulako University consider very poor. Students were not brave in expressing their opinion, they tend to be silent during the learning process.This research intends to improve speaking skill through the application of digital storytelling. This is a quasi-experimental non-equivalent control group design. The population of this research was 20 first semester students at international class of Communication Science Department, Tadulako University. This research was conducted in 16 meetings during the first semester. The variable was speaking skill and technique applied was digital storytelling. Data showed that score of t-counted (3.3) is higher than the t-table (2.00). It means that the hypothesis is accepted. Therefore, it can be concluded that Digital storytelling can improve speaking skill.